SEJARAH MASUKNYA ISLAM DI INDONESIA - Deni Firdaus; Anzil Alaina Maidah, Alfin Laila Rahmawati, Ahmad Maftuh Sujana (CV. Adiba Aisha Amira, 2025)
Islam has played a central role in shaping the historical and cultural identity of Indonesia. Its introduction and gradual dissemination occurred through peaceful means and various channels, including trade, the preaching of scholars and Sufi missionaries, intermarriage, and political endorsement from local rulers. This article aims to analyze the Islamization process in the Indonesian archipelago using a historical and descriptive-analytical approach, drawing upon both primary and secondary sources. The findings suggest that Islam was first introduced by Muslim traders from Arabia, Persia, and India as early as the 7th century CE, with major port cities in Sumatra and Java serving as key entry points. The study explores competing theories on the origins of Islam in Indonesia, namely the Arab, Gujarat, Persian, and Chinese theories and examines the cultural, political, and social factors that shaped its acceptance. The research concludes that the success of Islamization in Indonesia is closely linked to the religion’s flexibility, the accommodative methods of da'wah tailored to local traditions, and the integration of Islamic values into social and political systems